2009
DOI: 10.1111/j.1365-2753.2008.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy in emergency departments: Australian practice

Abstract: 30 subjects (58% response rate) from 21 sites participated. Mean age 30.4, 29 females, one male and an average of 9-year clinical experience. OT service was usually provided within multidisciplinary or interdisciplinary teams by full-time employed staff and patients were overwhelmingly Australian Triage Scale level 4 or 5 and were over 65 years. Few standardized assessment or outcome measures were used. The OT role was consistently focussed on functional assessment and provision of interventions such as equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…Variations were present in what occupational therapists reported addressing compared to what was actually addressed in therapy due to the challenges that prevented comprehensive assessment of instrumental activities of daily living (IADL) (i.e., home management skills, financial management, transportation, and driving) in the acute care environment (Crennan & MacRae, 2010). Similarly, studies on occupational therapy assessment and discharge planning in the emergency department setting, which also serves a high proportion of elderly clients within a limited time frame, reported a lack of standardized assessments and the use of functionbased or "in-house" tools in order to make discharge recommendations (Carlill, Gash, & Hawkins, 2004;Cusick, Johnson, & Bissett, 2008;Veillette, Demers, & Dutil, 2007). Jette et al's (2003) study concluded that although the discharge planning process was largely guided by patients' functioning and disability, wants and needs, ability to participate in care, and life context, the limited time frames prevented the overt use of standardized assessments.…”
Section: Assessment For the Elderly In Acute Carementioning
confidence: 98%
“…Variations were present in what occupational therapists reported addressing compared to what was actually addressed in therapy due to the challenges that prevented comprehensive assessment of instrumental activities of daily living (IADL) (i.e., home management skills, financial management, transportation, and driving) in the acute care environment (Crennan & MacRae, 2010). Similarly, studies on occupational therapy assessment and discharge planning in the emergency department setting, which also serves a high proportion of elderly clients within a limited time frame, reported a lack of standardized assessments and the use of functionbased or "in-house" tools in order to make discharge recommendations (Carlill, Gash, & Hawkins, 2004;Cusick, Johnson, & Bissett, 2008;Veillette, Demers, & Dutil, 2007). Jette et al's (2003) study concluded that although the discharge planning process was largely guided by patients' functioning and disability, wants and needs, ability to participate in care, and life context, the limited time frames prevented the overt use of standardized assessments.…”
Section: Assessment For the Elderly In Acute Carementioning
confidence: 98%
“…Typical CPD activities include journal reviews, in‐service training, personal reflection, short courses, conferences, clinical interest group membership, quality assurance projects and literature searching (Alsop, 2000). While the current literature provides an emerging evidence base for ED occupational therapy practice (Carlill, Gash & Hawkins, 2002; Cusick, Johnson & Bissett, 2009; Hendriksen & Harrison, 2001; Johnson & Cusick, 2009; Smith & Rees, 2004; Veillette, Demers & Dutil, 2007; Veillette, Demers, Dutil & McCusker, 2008), no literature was found exploring ED occupational therapy CPD. This study helps fill the gap by identifying factors relevant to CPD planning.…”
Section: Introductionmentioning
confidence: 99%
“…, 2002). Older people are the primary service recipients of allied health services in ED (Anaf & Sheppard, 2007; Cusick et al. , 2009; Veillette et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations